Nibble, cut, stomp and burn: Biodiversity effects of disturbances in fen grassland. Issue 2 (4th June 2022) - Fløjgaard, Camilla; Brunbjerg, Ane Kirstine; Andersen, Dagmar Kappel; Dalby, Lars; Lehmann, Louise Juhl; Bruun, Hans Henrik; Ejrnæs, Rasmus
Abstract: Aims: We assessed biodiversity effects of disturbance in meadows and rich fens. We hypothesized that disturbances and their timing affect plant and bryophyte species richness and other indicators of conservation success. More specifically, we expected conservation status to improve with disturbances that mimic natural grazing processes, that is, that extensive year‐round grazing with trampling had a more positive effect than intensive summer grazing or mowing. Location: Kastbjerg wetlands, Jutland, Denmark. Methods: In a three‐year field experiment, we applied trampling, season‐specific defoliation with biomass removal and burning in a randomized design in nine wetland sites. We recorded species richness and community composition. Bayesian generalized linear mixed‐effects models were built with treatment as fixed effect, site as random effect and species richness or species composition as responses. Leaf N and P, and soil moisture were included as covariables. Further, a quadratic discriminant analysis (QDA) was applied to test for discrimination between treatments based on a set of biodiversity indicators. Results: Environmental and biotic differences among sites were considerable and significant indicating a considerable effect of historical contingency (local species pool). We found only minor and mostly insignificant effects of disturbance on vegetation. However, a QDA revealed significant differences among treatments based on five indicators for conservation status. Simulated grazing and trampling were generally associated with higher vascular plant richness, bryophyte richness, number of indicator species and stress‐tolerant species and decreasing abundance of competitive species. Conclusion: We found small, but positive effects of disturbance on biodiversity indicators of wetland vegetation after three years of experimental treatments. Initial site differences explained most variation, indicating strong historical contingency. Our results support the need for restoration of disturbances in fens and meadows, and the importance of prioritizing areas with near‐natural biotas. Abstract : After a three‐year experiment of simulated grazing, trampling and burning, we found small, but positive effects of disturbance on biodiversity indicators of wetland vegetations, but also strong historical contingency. This supports the need for grazing management in wetlands and the importance of prioritizing areas with near‐natural biotas to ensure biodiversity conservation.